Ocorrência de agravos músculo - esqueléticos em áreas públicas de lazer : a experiência da pista de saúde da Universidade Federal de São Carlos - Simões, Nelcy Vera Nunes (Universidade Federal de São Carlos, 2008)
This study objectives were to characterize and identify the occurrence of muscle skeletical injury on physical activity praticers that make use of the Health Track at the Federal University of São Carlos (HT/UFSCar). The study was a nonprobabilistic descriptive observation sample of individuals who makes use of the HT/UFSCar. There were 376 subjects 220 male and 156 female, between 11 and 82 years old. The data was collected during six consecutive months. The statistic work included as much variables of descriptive analyses as the study of their possible association and then applied to the parametric test Qui-square of Pearson. The results showed that from the 376 subjects, 126 (33,51%) subjects suffered injuries during the observation while 250 (66,49%) did not. It was also verified that variables such as : Frequency, Intensity, Duration, Physical Activity, Gender, Body Mass, School Degree and Social Class are significantly associate to the incidence of injuries to the public users at the HT/UFSCar. Still, the men practiced more physical activities and suffered more injuries than the women. Conclusion: The association between the investigated variables (overweight, number of turns at the track, social class and the frequency at the HT/UFSCar - over 5 times per week) and the type of PA practiced were significant to injuries occurred (57.48%) during the development of this study.
Keywords: Lesões músculo-esqueleticas; Atividade física; Saúde pública; Lazer; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL